Earliest evidence for systematic use of ultrahigh carbon steel in the ancient Aegean in the Archaic Milesia. - Ümit Güder; Jana Mokrišová; Marek Verčík; Ünsal Yalçın (PLoS ONE)
This study presents the results of archaeometallurgical investigation of iron objects from the Sanctuary of Apollo in ancient Didyma, dating to the Archaic period (7th to the early 5th centuries BCE). The analysed precision work tools and semi-formed objects exhibit distinct material characteristics that differentiate them from other iron-steel artefacts of both small and large formats (weapons, implements, and architectural fittings) so far investigated in the Aegean. They were made of medium, high, and ultra-high carbon steel. Three objects belonging to this latter category consist of remarkably clean, homogeneous, and high-quality steel. After presenting the analytical results, this article discusses various explanatory models for the production of these objects and attempts to answer questions about the motivations for this innovation, highlighting their functional characteristics and context of production and consumption.